2008
DOI: 10.1179/joc.2008.20.2.180
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEvaluation of the Antimicrobial Activity of Meropenem in Combination with Polymyxin B and Gatifloxacin AgainstPseudomonas aeruginosaandAcinetobacter baumannii

Abstract: The antimicrobial activity of meropenem combined with either polymyxin B or gatifloxacin was evaluated by the checkerboard method against Pseudomonas aeruginosa (10 strains) and Acinetobacter baumannii (10 strains). In addition, the triple combination of polymyxin B, gatifloxacin, and meropenem was also studied as well as the polymyxin B and gatifloxacin combination. A partial synergism interaction between meropenem and polymyxin B was observed for 80% of the A. baumannii strains. In contrast, this combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
5
1
1
Order By: Relevance
“…For meropenem–polymyxin B combinations ( Figure 6 ), tests were carried out on 99 strains in four studies, and showed a pooled synergy rate of 37.0% (95% CI, 0.0%–100.0%) and heterogeneity ( I 2 ) was 98.1%. 13 , 26 , 39 , 51 Owing to its high heterogeneity, we used the random-effect model for statistical analysis. No isolates were found to be antagonistic.…”
Section: Resultsmentioning
confidence: 99%
“…For meropenem–polymyxin B combinations ( Figure 6 ), tests were carried out on 99 strains in four studies, and showed a pooled synergy rate of 37.0% (95% CI, 0.0%–100.0%) and heterogeneity ( I 2 ) was 98.1%. 13 , 26 , 39 , 51 Owing to its high heterogeneity, we used the random-effect model for statistical analysis. No isolates were found to be antagonistic.…”
Section: Resultsmentioning
confidence: 99%
“…indifference as 4≥∑FIC>1 and antagonism as ∑FIC>4 (Fernandez-Cuenca et al, 2003, Guelfi et al, 2008, Kiffer et al, 2005, Timurkaynak et al, 2006, or 4. Synergy as ∑FIC≤0.5; additive as 1≥∑FIC>0.5 and antagonism as ∑FIC≥4 (Manikal et al, 2000), or the combination MIC of one of the antimicrobials is less than its susceptible breakpoint.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in our laboratory demonstrated an indifferent effect for the combination of polymyxin B and meropenem for 80% of the P. aeruginosa strains tested. In addition, no change in MIC values was observed in the meropenem-resistant strains [11].…”
Section: Resultsmentioning
confidence: 98%
“…The drug combination tests were evaluated by the checkerboard method [11] in 96-well microtitre plates (Inlab, São Paulo, Brazil). Polymyxin B and colistin were tested alone and in association with multiples and fractions of the MICs of ceftazidime, cefepime and piperacillin.…”
Section: Evaluation Of the Antimicrobial Activity Of The Combinationsmentioning
confidence: 99%